Grain Boundary and Interface Passivation with Core–Shell Au@CdS Nanospheres for High‐Efficiency Perovskite Solar Cells. (5th February 2020) - Qin, Pingli; Wu, Tong; Wang, Zhengchun; Xiao, Lan; Ma, Liang; Ye, Feihong; Xiong, Lun; Chen, Xiangbai; Li, Haixia; Yu, Xueli; Fang, Guojia
Abstract: The plasmonic characteristic of core–shell nanomaterials can effectively improve exciton‐generation/dissociation and carrier‐transfer/collection. In this work, a new strategy based on core–shell Au@CdS nanospheres is introduced to passivate perovskite grain boundaries (GBs) and the perovskite/hole transport layer interface via an antisolvent process. These core–shell Au@CdS nanoparticles can trigger heterogeneous nucleation of the perovskite precursor for high‐quality perovskite films through the formation of the intermediate Au@CdS–PbI2 adduct, which can lower the valence band maximum of the 2, 2, 7, 7‐tetrakis( N, N ‐di‐ p ‐methoxyphenyl‐amine)9, 9‐spirobifluorene (Spiro‐OMeTAD) for a more favorable energy alignment with the perovskite material. With the help of the localized surface plasmon resonance effect of Au@CdS, holes can easily overcome the barrier at the perovskite/Spiro‐OMeTAD interface (or GBs) through the bridge of the intermediate Au@CdS–PbI2, avoiding the carrier accumulation, and suppress the carrier trap recombination at the Spiro‐OMeTAD/perovskite interface. Consequently, the Au@CdS‐based perovskite solar cell device achieves a high efficiency of over 21%, with excellent stability of ≈90% retention of initial power conversion efficiencies after 45 days storage in dry air. Abstract : Au@CdS fills in the perovskite grain boundaries to form an Au@CdS–PbI2 intermediate, which increases the valence band maximum of Spiro‐OMeTAD for a more favorable energy alignment with perovskite. With the help of the localized surface plasmon resonance of Au@CdS, the holes easily overcome the interface barrier through the bridge of the intermediate Au@CdS–PbI2 . The corresponding device shows high performance.